Aspiration Pneumonia: Patophysiology, Diagnosis and Treatment - Kirana, Devi Chandra; Fathana, Prima Belia; Ristia, Ovia Intan; Mario, Andina Nabilah; Lukman, Dian Azizah; Abdiman, I Made Tobias; Putra, Made Raditya Arhya; Salsabila, Maida Sania (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Aspiration pneumonia is one of the diseases that is often hidden and under-recognized. This disease contributes to a higher mortality rate compared to other types of pneumonia. This study aims to analyze the pathophysiology, diagnosis and management of aspiration pneumonia. The method used is a literature study by searching for literature published in PubMed, ScienceDirect, and Researchgate with the keywords